Legal nature of the crimes at Paris. Terrorism or war crimes? - Campusano Droguett, Raúl F.; Acevedo Espínola, Luis Hernán (Revista Tribuna Internacional, 2017)
In this text we analyse from a legal point of view, the crimes committed in Paris on November 13th of 2015 by the criminal organization ISIS. As a general perception, these acts are understood as “acts of terrorism”, witch we think it is not the best option, not only because there is not an international definition of “acts of terrorism”, but also because the definitions domestic legislation use for such kind of acts are technically wrong and usually affect the due process of law. We think, as a second option, that these acts are actually war crimes under the Rome Statute of 1998 and the Geneva Convention with their Additional Protocols, which could become an effective option under procedure law.